PEMANASAN GLOBAL, SKEMA GLOBAL DAN IMPLIKASINYA BAGI INDONESIA - Forqan, Berry Nahdian (Jurnal Legislasi Indonesia, 2009)
Indonesia has been the focus of much international attentionover recent years due to its increasingly prominent role increating greenhouse gas emissions. It has emerged the thirdhighest carbon dioxide emitting country in the world after theUnited States and China. During the meeting of the 13thConference of the Parties (COP-13) to the United NationsFramework Convention on Climate Change (UNFCCC) in Baliin 2007, Reducing Emissions from Deforestation and ForestDegradation in Developing countries (REDD) emerged as aprominent component of any future efforts to mitigate climatechange. REDD aims to stabilise the atmospheric concentrationof CO2 at as low a level as possible through a system offinancial reward for halting or slowing rates of deforestation.But in the reality, what is happen now is only about emissiontrading. Another concern with linking REDD to markets relatesto the issue of national sovereignty over natural resources. Bothat the national and community levels we may see a loss ofautonomy over natural resources as third parties gain increasinginfluence over natural resource decisions. There is significantinconsistency between stated government aims regarding forestprotection and official government policy. While the governmentpublicly declares its intentions to effectively tackle climatechange and reduce forest destruction, it just the last 12 monthsit has established a number of damaging regulations whichseek to do just the opposite. And Finally, in February 2009,the Agriculture Ministry issued a decree allowing businessesto convert millions of hectares of peatlands into oil palmplantations. Opening up these peatland areas risks releasinghuge amounts of CO2 into the atmosphere. The decree hasbeen conditionally approved by the Environment Minister andis expected to go into force later this year. The decision isstrangely at odds with the Agriculture Ministry’s previous position - in 2007 it released a letter asking governors to stopthe conversion peatlands into oil palm plantations. This starkcontradiction has led to claims that the government is attemptingto satisfy powerful business interests in the lead up to thegeneral election later this year.The Indonesian government’scommitment to real and meaningful reductions in deforestationmust be seriously questioned when such glaring inconsistenciesabound.